Design, development and evaluation of The Manila City Library Software a library orientation and instruction program - Bartolome, Sharon G.; Panopio, Dennis P.; Cabbab, Johann Frederick A. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2002)
The Manila City Library Software was developed to aid users in their library search. It was developed to study its acceptability and usability. The program consists of four parts: a. profiles features the library's organizational goals, history, department functions, library service outlets, hours of operation, library activities and public library service; browse titles; c. maintenance; c. exit.
A total of 104 respondents were asked to evaluate the software. After using the program, ninety-four (90.3 percent) knew more of the library's history. Ninety (86.5 percent) knew more of the library's rules and regulations. All of the respondents answered that they knew more of the library's projects and activities, while 100 (96.1 percent) knew more of the library's other branch libraries.
Eighty-five (81.7 percent) answered that the program was easy to use, eighty-nine (85.5 percent) said that it was informative, ninety-four (90.3 percent) respondents answered that it have helped in their research, eighty-five (81.7 percent) respondents agreed that the program can maintain interest, ninety-eight (94.2 percent) said that they're going to use the program gain while all respondents answered that they're going to recommend the program.
Library personnel were also asked about their perception of the program. Specifically, they were asked about the maintenance part of the program. Twenty (20) of them answered that the program was easy to use, twenty-five (25) answered that the program was informative, twenty-three (23) respondents said that it was helpful, while twenty-three (23) said it was interesting. Sixteen (16) respondents answered that the program was easy to maintain.
Vita.
Thesis (Bachelor of Library Science)--University of the Philippines Diliman
Keywords: Manila City Library; Computer software -- Philippines -- Development